American experimental poetry and democratic thought - Marshall, Alan, Dr. (Oxford : Oxford University Press, 2009)
Alan Marshall examines the nature of democratic thought and expression in American experimental poetry, from Walt Whitman in the mid-19th century to George Oppen and Frank O'Hara in the mid-late 20th.
Includes bibliographical references.
Description based on print version record.
Keywords: Experimental poetry, American -- 19th century -- History and criticism; Experimental poetry, American -- 20th century -- History and criticism; Democracy in literature